Seismic Waves Probing Earth System - Kanao, Masaki; Toyokuni, Genti (IntechOpen, 2019)
The importance of seismic wave research lies not only in our ability to understand and predict earthquakes and tsunamis, but it also reveals information on the Earth's composition and features in much the same way as it led to the discovery of Mohorovicic's discontinuity. As our theoretical understanding of the physics behind seismic waves has grown, physical and numerical modeling have greatly advanced and now augment applied seismology for better prediction and engineering practices. This book demonstrates the latest techniques and advances in seismic wave analysis from a theoretical approach, data acquisition and interpretation, to analyses and numerical simulations, as well as research applications. The major topics in this book cover aspects on seismic wave propagation, characteristics of their velocities and attenuation, deformation process of the Earth's medium, seismic source process and tectonic dynamics with relating observations, as well as propagation modeling of seismic waves.